ENGLISH AS A FOREIGN LANGUAGE LESSON PLANS DURING COVID-19 PANDEMIC IN THE SENIOR HIGH SCHOOL - Jayantari, N. L. P. E.; Agustini, D. A. E. (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Teachers have difficulties in preparing lesson plans that are adapted to online learning. This has resulted in students having difficulty learning English as a foreign language (EFL) through Google Classroom during the Covid-19 pandemic. The purpose of this study was to analyze the abilities and difficulties of teachers in preparing lesson plans and the difficulties of students in learning English as a foreign language (EFL) through Google Classroom during the Covid-19 pandemic. The design used in this research is the Embedded Mix Method design. The technique used to collect data is a questionnaire. The instrument used to collect data is a questionnaire. The population of this study found 10 teachers and 55 students. The ability of teachers to prepare lesson plans for EFL through Google Classroom is measured and described quantitatively. Meanwhile, the difficulties of teachers and students were described and analyzed qualitatively. The study results are the teacher's ability to prepare EFL lesson plans through Google Classroom, which is 67.50. It can be said that EFL teachers are less able to choose learning procedures or steps, choose learning media and evaluate learning. Students also have difficulty learning EFL through Google Classroom.